Challenges in establishing kindergarten education system in villages of Guizhou, China: A preliminary study - Keang-ieng P. Vong; Min Y. Li (South African Journal of Childhood Education, 2016)
The Miao ethnic group is among the 56 minority groups in China. Their ideas of education for young children differ from that of the mainstream education system in China. This study examines the scenario of early childhood education for Miao children living in villages of Guizhou Province. It discusses the history and traditions of the Miaos and the kinds and forms of education provided, but not necessarily desired, for their children between 3 and 5 years old. School principals and teachers responded to such issues, and visual data collected during a field trip to two different villages were used to triangulate the responses. Findings show that even though there has been a strong belief that links poverty to the opportunity of schooling, empirical evidence from this study cannot yet confirm this argument. Parents’ views of schooling were considered as influential factors. Nonetheless, challenges of early childhood education in rural areas, especially in underprivileged villages, of China are still inseparable from availability of resources and the government’s initiatives.